2021
DOI: 10.33963/kp.15899
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the remote monitoring of cardiac implantable electronic devices in 2021

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The way the medical service responds to alerts also has a great impact on outcomes; however, this requires adequate organization and resources in these centers to promote effective and immediate follow up. 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way the medical service responds to alerts also has a great impact on outcomes; however, this requires adequate organization and resources in these centers to promote effective and immediate follow up. 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…This argument is also used by some countries such as Canada, Portugal, and the United States to expand follow-up by RM. 24 , 30 RM published data in South America are scarce, and this study provides relevant information about the use of this form of follow-up in middle-income countries, thus contributing to the debate between medical societies and governments and allowing more patients to have in-home monitoring, especially high-risk groups. 16 …”
Section: Discussionmentioning
confidence: 99%
“…All parameter adjustments and responses to alarm events in the above studies were accomplished in the clinic follow-up ; (3) CIED programming cannot be carried out in time. The HomeGuide study found that the median time from remote event detection to clinical treatment was 3 days (1-14 days) 30 ; (4) It has been shown that remote monitoring reduces communication between patients and doctors and increases patient anxiety 33 .…”
Section: Follow-up After Cied Implantationmentioning
confidence: 99%